Assessment of soil compaction and shear strength of the side dam of the “Maziarnia” water reservoir - Andrzej Tadeusz Gruchot (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the study was to assess soil compaction of the side body of the “B” earth dam in the “Maziarnia” water reservoir in Wilcza Wola in the Podkarpackie Voivodeship by using a conical and a vane probe of a dynamic probing light. Shear strength parameters of soils embedded in the dam’s body were also determined, i.e. undrained shear strength basing on field tests and the angle of internal friction and cohesion in a direct shear apparatus.